Primary ovarian solid pseudopapillary neoplasm associated with familial adenomatous polyposis - McClaren, Alexandra; Syed, Basil; Syed, Sheeba (International Journal of Pathology, 2026)
Background: Solid pseudopapillary neoplasms (SPNs) are rare tumours, most often present in the pancreas. Extra-pancreatic SPNs are especially rare. Although FAP has not classically been associated with ovarian neoplasms, here we present the first documented case of a primary ovarian SPN in a patient with a known history of FAP.Case presentation: We report a patient who developed ovarian SPN on follow-up for FAP.  A 25-year-old female with a background of FAP presented with a large abdominal mass, raised serum Ca125. Subsequently, the right salpingoopherectomy microscopically and immunocytochemically confirmed a Solid pseudopapillary neoplasm.Conclusion: This case highlights awareness of possible occurrence of solid pseudopapillary neoplasm in the ovary in FAP patients. It is therefore important that SPNs are considered in the clinical and pathological differential diagnoses of tumors presenting in FAP patients.